Eating habits in students with sports specialization - Jana Juříková (Nicolaus Copernicus University in Toruń, 2020)
University studies with its increased psychological demands on all students in comparison to secondary schooling causes changes in their eating habits. Moreover, university degree programmes with sports focus may also be associated with increased physical load of students.               This work investigates students´ dietary habits at the Faculty of Sports Studies of Masaryk University in Brno (Czech Republic) using a questionnaire survey. 80 persons (45 men and 35 women) were randomly selected to participate in the survey. The average age of respondents was 20.18 years for men and 20.56 years for women. The average BMI was 24.48 for men and 22.01 for women. All subjects were found in the normal weight range according to BMI.               The findings of the questionnaire survey showed that while men typically (49.8%) eat 5 times a day, most women consume (65.7%) 4 daily meals. Furthermore, the frequency of consumption of main meals, i.e. breakfast, lunch and dinner, was examined. It is gratifying to find that most students - both men (66.7%) and women (65.7%) have breakfast daily, which is in agreement with nutritional recommendations. Lunch is considered the most important meal of the day. Lunch is also consumed by most respondents daily - the answers are the same as the answers to the previous question: 66.7% of men and 65.7% of women said that they have lunch daily. Concerning the consumption of dinners, most men (again 66.7%) have dinner daily, most women (34.3%) have dinner daily and the same number (34.3%) have dinner most days of the week, but not daily. Regarding the amount of fluids, most men (51.1%) reported that they drink 1.5-2 litres of fluids daily, while most women (66.7%) reported that they drink 2-3 litres of fluids daily. These results are related to the difficulty of various sport activities during the day.